EFFECTIVENESS OF STUDENTS PROPS IN LABOR SKILLS LABORATORY CONCERNING ASSESSMENT OF CERVICAL OPENING AND AMNITAL SKILL BREAKING - Aryani, Yeni; Susanti, Ari (JURNAL IBU DAN ANAK, 2024)
Research to produce products as teaching aids for clinical skills is still not widely carried out in midwifery education in Indonesia, especially low cost but high quality products. Research and development (R&D) in the form of student teaching aids in labor laboratory skills to assess cervical opening and breaking of membranes. After going through a series of R&D from the ADDIE (analyze, design, develop, implement, evaluate) method, the product was completed which involved quantitative and qualitative research (mixed method) in the evaluation stage. It is hoped that this product can be used as a student teaching aid with realistic, durable or cheap and safe characteristics. Research on a larger scale is needed as a follow-up action to R&D research in the mass trial stage. It is hoped that the government will increasingly support creative research, creation and product development of clinical skills teaching tools as a form of developing lecturers' creativity as quality teachers.